PENGARUH KEMAMPUAN SUMBER DAYA MANUSIA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA BADAN KESATUAN BANGSA DAN POLITIK KABUPATEN KONAWE SELATAN - Takwim Takwim (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
Abstract The design of this study used the explanatory research method, by testing the hypotheses that have been established through quantitative approaches and statistical tests. The samples used in this study were 55 people who were civil servants and PHT (Honorary) at the National Unity and Politics Board of South Konawe Regency. The sampling technique is by census that all populations are sampled as many as 55 people. The data analysis method used is multiple linear regression analysis. Data collection was carried out using a questionnaire as the main instrument addressed to respondents, and interviews with informants. Furthermore, this quantitative data is processed using correlation analysis, and multiple linear regression analysis. The results showed that the ability to positively influence the performance of employees at the National Unity and Politics Agency of South Konawe Regency. this means that abilities that include intellectual, physical abilities and the ability to cooperate with employees to carry out various tasks in a job in good condition will cause changes in employee performance towards a better direction.